(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Personal after integrated circuit technologies computers and the Internet, the Internet of Things are the most advanced technological systems. in the Republic of Uzbekistan information technology (IT), which is fundamentally changing business, is used in most industries as an automated system of technological computing. However, the impact of IoT on the manufacturing sector not yet fully explored. On the other hand, there are difficulties in working with existing computerized software tools complexity, dynamics and uncertainties in their application causes errors in modern enterprises. IoT and cloud adoption are highlighted computing in enterprise systems overcomes the challenge. In this article, the difficulties in creating technological system assembly plans complex products are discussed. IoT and cloud computing proposed to aid in the development of a traditional assembly modeling system to an advanced system capable of dealing with complexity and changes automatically. Meeting to achieve this goal the modeling system is automated and the proposed system includes and the following innovations: 1) modeled architecture the system is robust, reliable, flexible and scalable. 2) unified object-oriented templates to facilitate interfaces and reuse system components. 3) Automated algorithms for calculating technological system schemes relational assembly matrices are shown for assembly planning